Analysis of urban metabolism in an informal settlement using the MuSIASEM method in Lima - Acevedo De los Ríos, Alejandra (2024)
By 2050, 68% of the global population will reside in cities, driving rapid urban growth and intensifying demand for scarce ecological resources within the Water-Food-Energy nexus. Social metabolism quantifies energy and material transformations with a social focus, building upon urban metabolism. Its application in resource-scarce informal settlements (ISs) has the potential to enhance their sustainability significantly. As community dynamics evolve, acknowledging society as a dynamic variable within this framework becomes increasingly relevant. Our study employs the Multi-Scale Integrated Analysis of Societal and Ecosystem Metabolism (MuSIASEM) framework, focusing on key variables: human activity, land use, money, energy, water, waste, and food. Based on surveys, interviews, GIS datasets, and statistical information, the study investigates the Ciudad de Gosen IS in Lima, Peru. The results show that, in the socio-economic dimension, 43% of the time employed is directed to the unpaid work sector. Notably, 71% of women and 29% of men spend a mean of 44 h/week/person caring for children or elderly. In the paid work sector, there are gender asymmetries; men have a salary 54% higher than women. In the ecological dimension, more than 78% of the homes have access to basic services, unlike other informal settlements in Latin America and Africa. © 2024 The Authors